MicroRNA Expression Profile Identifies High Grade, Non-Muscle-Invasive Bladder Tumors at Elevated Risk to Progress to an Invasive Phenotype - Lenherr, Sara M. (Genes (Basel), 2017)
The objective of this study was to identify a panel of microRNAs (miRNAs) differentially expressed in high-grade non-muscle invasive (NMI; TaG3–T1G3) urothelial carcinoma that progress to muscle-invasive disease compared to those that remain non-muscle invasive, whether recurrence happens or not. Eighty-nine high-grade NMI urothelial carcinoma lesions were identified and total RNA was extracted from paraffin-embedded tissue. Patients were categorized as either having a non-muscle invasive lesion with no evidence of progression over a 3-year period or as having a similar lesion showing progression to muscle invasion over the same period. In addition, comparison of miRNA expression levels between patients with and without prior intravesical therapy was performed. Total RNA was pooled for microarray analysis in each group (non-progressors and progressors), and qRT-PCR of individual samples validated differential expression between non-progressive and progressive lesions. MiR-32-5p, -224-5p, and -412-3p were associated with cancer-specific survival. Downregulation of miR-203a-3p and miR-205-5p were significantly linked to progression in non-muscle invasive bladder tumors. These miRNAs include those implicated in epithelial mesenchymal transition, previously identified as members of a panel characterizing transition from the non-invasive to invasive phenotype in bladder tumors. Furthermore, we were able to identify specific miRNAs that are linked to postoperative outcome in patients with high grade NMI urothelial carcinoma of the bladder (UCB) that progressed to muscle-invasive (MI) disease.